2013
DOI: 10.3166/rfg.234.151-166
|View full text |Cite
|
Sign up to set email alerts
|

La participation ordinaire. Mieux comprendre le vécu du consommateur pour faciliter son adhésion

Abstract: Distribution électronique Cairn.info pour Lavoisier. © Lavoisier. Tous droits réservés pour tous pays.La reproduction ou représentation de cet article, notamment par photocopie, n'est autorisée que dans les limites des conditions générales d'utilisation du site ou, le cas échéant, des conditions générales de la licence souscrite par votre établissement. Toute autre reproduction ou représentation, en tout ou partie, sous quelque forme et de quelque manière que ce soit, est interdite sauf accord préalable et écr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Another research avenue suggested by this study is the perceived complexity of recycling. Recycling logistics does not appear to be self-evident, despite what the literature on 'ordinary' activities would lead us to believe (Benoit-Moreau et al, 2013;Dujarier, 2008), because it requires a certain number of different activities to be coordinated. Nonetheless, our data does not include information with regard to perceived complexity.…”
Section: Research Perspectivesmentioning
confidence: 99%
“…Another research avenue suggested by this study is the perceived complexity of recycling. Recycling logistics does not appear to be self-evident, despite what the literature on 'ordinary' activities would lead us to believe (Benoit-Moreau et al, 2013;Dujarier, 2008), because it requires a certain number of different activities to be coordinated. Nonetheless, our data does not include information with regard to perceived complexity.…”
Section: Research Perspectivesmentioning
confidence: 99%